Tourism Policy During the New Normal Period in Tomohon City - Pontonuwu, Daniel Elvis; Bogar, Wilson; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
The emergency status caused by Coronavirus Diseases (Covid-19) has prompted the government to implement Social Distancing as a measure to reduce the number of spreads of the Covid-19 virus. Social distance is a person’s efforts not to interact at close range or avoid crowds. The community is asked to work at home, study from home and worship at home; even tourist attractions are not allowed to operate, this situation is a challenge for tourism actors. The purpose of this study is to find out how the tourism strategy is during the New Normal period after the COVID-19 pandemic with restrictions on community activities. This study uses a qualitative approach. Data analysis was carried out with qualitative-interpretive. The results of research conducted at the prayer hill religious area show that government policies through the implementation of Government Regulation No. 1 of 2021 concerning Improving Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019 have been well implemented in terms of four indicators, namely: communication, resources, disposition and bureaucratic structure.